2020
DOI: 10.1111/jsap.13144
|View full text |Cite
|
Sign up to set email alerts
|

Effect of breed as a risk factor for humeral condylar fracture in skeletally immature dogs

Abstract: Objectives To investigate the effect of breed as a risk factor associated with humeral condylar fracture in skeletally immature dogs in the UK. Materials and Methods Retrospective study of dogs under 12 months of age that were presented with humeral condylar fracture to three specialist referral centres between 2015 and 2018. Data retrieved from medical records included breed, age, gender, neuter status, affected limb, fracture configuration and aetiology of the fracture. Breed population percentages were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
49
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(62 citation statements)
references
References 15 publications
7
49
6
Order By: Relevance
“…Additionally in the American Cocker Spaniel, pedigree analysis of eight dogs suggested a genetic basis for humeral intracondylar fissure with a recessive mode of inheritance. 13,17 While French Bulldogs have been reported as being a breed predisposed to HCF in older literature, 9 recent literature has shown large increases in the prevalence of this condition in this breed 1,19 with the current study showing French Bulldogs being 49.3 times more likely to develop HCF compared with the general population. The median age at presentation for HCF in French Bulldogs was 5 months of age with 75% occurring at 6 months of age or less, consistent with current literature.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…Additionally in the American Cocker Spaniel, pedigree analysis of eight dogs suggested a genetic basis for humeral intracondylar fissure with a recessive mode of inheritance. 13,17 While French Bulldogs have been reported as being a breed predisposed to HCF in older literature, 9 recent literature has shown large increases in the prevalence of this condition in this breed 1,19 with the current study showing French Bulldogs being 49.3 times more likely to develop HCF compared with the general population. The median age at presentation for HCF in French Bulldogs was 5 months of age with 75% occurring at 6 months of age or less, consistent with current literature.…”
Section: Discussionmentioning
confidence: 49%
“…The breed disposition reported in this study are consistent with recently published studies, with several notable differences. Sanchez Villamil and colleagues, 1 and Smith and colleagues 19 both similarly reported in 2020 that French Bulldogs and Spaniel breeds are predisposed to HCF compared with other breeds 1,19 however, these studies did not find English Bulldogs and Boston Terriers to be predisposed. Furthermore, Sanchez Villamil and colleagues reported that French Bulldogs were at increased risk of medial HCF, 1 which is in stark contrast to the current study in which no French Bulldogs presented for medial HCF.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This may be because the mean age of the cohort in this study was above that reported for French bulldogs suffering FLHC, different predisposing factors for FLHC in French Bulldogs compared with Spaniel breeds or because this study excluded fractures of the medial aspect of the humeral condyle. [19][20][21] The lateral aspect of the distal humerus is a challenging area in which to apply a plate due to the required contouring. Additionally, plate screws directed lateral-medial toward the anconeal fossa must be short or monocortical to avoid impinging on the anconeal process.…”
Section: Discussionmentioning
confidence: 99%